La Construcción de una Visión de Futuro para la guadua: desde la cadena productiva hacia el cluster de la guadua en el eje cafetero (2019)
This paper outlines the main results and the methodologicalprocess to build a technology road map for the bamboo clusterin the Colombian coffee zone